THE USE OF SHORT ANIMATED MOVIE OF FOLKTALE IN TEACHING WRITING NARRATIVE TEXT - Maria Clara Cinthya; Endang Susilawati; Syarif Husin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract The aim of this research was to find out the effectiveness of short animated movie of folktale in teaching writing narrative text to eleventh grade students of SMAK Abdi Wacana Pontianak in academic year 2018/2019. This research used Pre Experimental in one group pre-test and post-test design. The researcher took the sample by using cluster random sampling to determine the participant of research which consisted of 26 students. The data was collected by using measurement technique in form of writing test. Through written test,it can be revealed that short animated movie of folktale increased students’ achievement in writing narrative text. The findings showed that the effect size of the treatment was 1.1. It was categorized as a very strong effect (ES > 0.8). To conclude, short animated movie of folktale has a very strong effect to increase the ability in writing narrative text. Key Words: Short Literacy Movie, Narrative Text, Writing